Evaluating mitigation strategies for urban heat island in Mandaue City using ENVI-met - Aiza Cortes; Arnold Jesfel Rejuso; Justine Ace Santos; Ariel Blanco (Journal of Urban Management, 2022)
Mandaue is a crucial city in Cebu island, Philippines as it links other large metropolises and is highly industrialized. The occurrence of urban heat island (UHI) in Mandaue was already confirmed by a previous study. In this paper, we aim to determine how UHI in Mandaue could be improved by mitigations including increasing vegetation, adding open spaces, employing green roofs and/or a combination thereof. ENVI-met software was utilized to simulate two study sites: M. C. Briones street and the planned urban development (PUD). To reduce computing load, M. C. Briones street was further divided into 2 subareas and PUD into 4 subareas. Results of the simulation indicate that addition of more urban spaces and trees could decrease air temperature by 0.2~​êC on average while green roof could decrease air temperature by an average range of 0.2~​êC-0.4~​êC. When a combination of trees, grasses and green roof is used, air temperature could be decreased by an average range of 0.1~​êC-0.3~​êC. Despite these mitigations, thermal comfort index in Mandaue would still be greater than 26~​êC which means that majority of the people would feel uncomfortable. On the other hand, addition of more urban spaces and trees could decrease surface temperature by an average range of 0.5~​êC-0.8~​êC while conversion of building roofs into green roofs would have no effect. When a combination of vegetation and green roof is employed, surface temperature could be decreased by an average range of 0.4~​êC-1.1~​êC.
Keywords: 710; Climate scenarios; Three-dimensional simulation; Urban design; Urban warming